ANALISIS SAMBARAN PETIR PADA TIANG TRANSMISI DENGAN MENGGUNAKAN METODE LATTICE - Abduh, Syamsir (Jurnal Teknik Elektro, 2002)
Power systems are often subjected to overvoltages that have their origin in atmosphericdischarges in which case they are called external or lightning overvoltages. Ligthningovervoltages remain essentially independent of the systemâs design such as transmissionstower. Owing to the complexity of a the lightning phenomenon, simulation experiment hasbeen an important method to resolve such phenomenon. However, it is difficult to simulatethe distribution of lightning striking points. Previous lightning simulation expriment canâtwell reflect the influence of lighning strength and direction on striking. The paper presentsthe Lattice Method to analyze lightning phenomenon strength especially for the transmissiontowerKeyword: lightning phenomenon, lattice method, transmission tower.